Formulation of Criminal Liability of Corporations Perpetrating Criminal Acts of Terrorism in Law Number 1 of 2023 concerning the Criminal Code: Formulasi Pertanggungjawaban Pidana Korporasi Pelaku Tindak Pidana Terorisme dalam Undang-Undang Nomor 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana - Dede Indraswara (Annual Review of Legal Studies, 2024)
Corporations as subjects of criminal law can be held criminally responsible for corporations as perpetrators of terrorism. In Indonesia, the regulation of Terrorism outside the Criminal Code recognizes that corporate subjects are only those with legal entities and those without legal entities, without knowing the types and application of appropriate criminal penalties. The ratification of Law Number 1 of 2023 concerning the Criminal Code (Indonesian Criminal Code) provides a complement to the criminal liability of corporations that commit acts of terrorism (terrorist corporations) which regulates the type of legal entity, ownership status and legal entity status. In addition, for corporations that have been subject to criminal sanctions, there is still a gap in corporate criminal liability related to the spread of radical corporate teachings. This shows that there is a legal gap between das sein and das sollen related to the type of legal entity, ownership status, legal entity status that has not been regulated in the Terrorism Law, the Terrorism Financing Law and criminal liability for radical corporate teachings in the Indonesian Criminal Code. Research shows that the ideal corporate criminal liability is to form a variety of corporate qualifications so that they are relevant to current needs. In addition, terrorist corporations that have been declared banned often still have significant influence and transform into new entities, so granting legal status that prohibits radical teachings from developing and being disseminated can be a form of accountability for terrorist corporations that embodies a sense of justice.